2022
DOI: 10.1590/s1677-5538.ibju.2020.0548
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of efficacy of three commonly used alpha-blockers as medical expulsive therapy for distal ureter stones: A systematic review and network meta-analysis

Abstract: Introduction:The efficacy of alpha-blockers as medical expulsive therapy (MET) is well established. However, it is not known which of the three most commonly used alphablockers (tamsulosin, alfuzosin and silodosin) is the most efficacious. With this study we aimed to assess the efficacy of the three commonly used alpha-blockers as MET for distal ureter stones. Materials and Methods: For this review, we searched multiple databases such as PubMed/Medline, Scopus, Embase, OviD SP, CINAHL, and web of science to id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 51 publications
0
13
2
Order By: Relevance
“…Furthermore, the findings of another meta-analysis demonstrated that silodosin was the most efficacious alpha-blocker as MET for distal ureteric stones (19). The results of two meta-analyses suggest that silodosin is more effective than tamsulosin for the spontaneous stone pass (19,22). However, in our study, we did not identify a better expulsion rate as MET with silodosin than with tamsulosin.…”
Section: Discussioncontrasting
confidence: 76%
See 2 more Smart Citations
“…Furthermore, the findings of another meta-analysis demonstrated that silodosin was the most efficacious alpha-blocker as MET for distal ureteric stones (19). The results of two meta-analyses suggest that silodosin is more effective than tamsulosin for the spontaneous stone pass (19,22). However, in our study, we did not identify a better expulsion rate as MET with silodosin than with tamsulosin.…”
Section: Discussioncontrasting
confidence: 76%
“…The others demonstrated that alpha-blockers had a significantly higher stone expulsion rate when compared to placebo (17,18). Despite contradictory results, a recent meta-analysis showed that there was a significantly better expulsion rate and lower mean expulsion time in tamsulosin, alfuzosin, and silodosin groups compared to placebo (19). The success rate for tamsulosin in distal ureteral stones smaller than 10 mm ranges between 50% and 87% (7,9,16,17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metaanalysis describing the efficacy of Silodosin and medical expulsive therapy evaluated the effect on pain management as pain episodes declined with Silodosin treatment and spontaneous passage of stones were increased within the first 14 days of treatment. 5,22,23 Silodosin has not been fully evaluated in the paediatric population as medical expulsive therapy, this study will be a beneficial contribution in literature especially in a developing country population where paediatric urolithiasis is on expansion and ongoing. The limitations of this study are a smaller sample size, and no CT KUB has been performed to assess the ureteric stones due to financial restraints.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of postural hypotension was similar with all the drugs, whereas silodosin emerged as the most efficacious drug as MET for lower ureter stones. 124 The same researchers reported that a tadalafil plus silodosin combination and silodosin as an individual drug are the best for treating lower ureter stones considering the SET and SER. 125 A meta-analysis carried out by Liu et al reported similar findings stating that tadalafil plus silodosin has the highest probability of reducing SET, and treating ureteral stones ≤10 mm.…”
Section: Methodsmentioning
confidence: 99%